2007
DOI: 10.1016/j.canlet.2007.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen tension on CD133 phenotype in human glioma cell cultures

Abstract: Under standard culture conditions, tumor cells are exposed to 20% O(2), whereas the mean tumor oxygen levels within the tumor are much lower. We demonstrate, using low-passaged human tumor cell cultures established from glioma, that a reduction in the oxygen level in these cell cultures dramatically increases the percentage of CD133 expressing cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
105
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(119 citation statements)
references
References 18 publications
9
105
1
4
Order By: Relevance
“…2A). Similar results of CD133 + U87 cells in free-floating culture conditions have been published previously [6,21].…”
Section: Resultssupporting
confidence: 77%
“…2A). Similar results of CD133 + U87 cells in free-floating culture conditions have been published previously [6,21].…”
Section: Resultssupporting
confidence: 77%
“…However, in the primary GBM cells the mRNA levels were substantial, indicating that low protein level may be due to a possible translational and/or posttranslational control. Culture conditions, including exposure to serum, have been hypothesized to affect CD133 expression or glycosylation (19). This could potentially explain why our primary GBM lines had less CD133 glycosylation-positive cells than others have reported.…”
Section: Discussionmentioning
confidence: 80%
“…The conflicting evidence casts doubt on CD133 as a cancer stem cell marker. CD133 has been analyzed via several methods including Western blot analysis, immunomagnetic (MACS), and fluorescence-activated cell sorting (FACS) (1,18,19), however the vast majority of CD133 research is carried out using the AC133 monoclonal antibody, and to a lesser extent the 293C monoclonal antibody (2,(4)(5)(6)12), both of which detect glycosylated epitopes of CD133. Recent research (20) has shown that these antibodies are not specific for a glycosylated epitope, and that AC133 can detect protein with mutated glycosylation sites, as well as non-glycosylated recombinant CD133 protein.…”
Section: Introductionmentioning
confidence: 99%
“…C'est ainsi que les conditions de culture « classiques » (20 % O 2 ) apparaissent aujourd'hui préjudiciables au maintien des cellules souches qui requiert un pourcentage proche de 1-3 % [2,[11][12][13]. Par ailleurs, dans le cas des tumeurs gliales du cerveau (glioblastomes), la diminution de la pO 2 favorise le maintien de la population exprimant la protéine CD133 en culture [14] -population à laquelle on attribue selon certaines publications un rôle critique en terme de tumorigéni-cité [15].…”
Section: Normoxie Expérimentale En Culture = Hyperoxie Physiologiqueunclassified